Design of heat exchanger for cooling fluid used on magnetic induction welder - Ekadewi A Handoyo; Lita Puspitasari (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
Magnetic induction welding is a common process in pipe production. The impeder used in the welding machine needs to be cooled to maintain its temperature below 35oC. The cooling fluid is water with 2% cutting oil and called coolant. It should enter the impeder at 15oC. The required flow rate is as much as 30 lt/min. To ensure the impeder’s temperature be kept lower than required temperature, then the heat exchanger shall be designed to cool the coolant from 40oC to 15oC. Air-cooled water chiller type UWAP750AY3 is used to produce chilled water needed by the heat exchanger. The 5/8-inch-finned-copper pipes are used as tubes in the heat exchanger. The coolant is divided in four equally tubes from a header. To meet the heat transfer area needed, each tubes will be bent to make 10 passes (or rows). At the end of the last row, four flow will be gathered in a header. Then, the coolant will circulate to impeder with the required temperature. Numerical simulation was conducted to get the velocity vector and temperature distribution of flow inside the tube, and also the pressure drop of the flow across the tubes and header. Velocity vector of flow around return bend, flow in entrance and exit are interesting. They give understanding that the pressure drop will be higher in such accessories than in straight pipe. The pressure drop of coolant flowing inside tubes of heat exchanger is 5143.2 Pa from analytical solutions and 4611.4 Pa from numerical simulation using Fluent. Temperature of coolant at outlet got from numerical simulation is almost the same with the designed temperature, i.e. 15oC. So, the numerical simulation reinforces the design of the heat exchanger.